2019
DOI: 10.1002/smll.201901156
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Amplification of Oxidative Stress–Mediated Antitumor Activity via Liposomal Dichloroacetic Acid and MOF‐Fe2+

Abstract: Cancer cells are susceptible to oxidative stress; therefore, selective elevation of intracellular reactive oxygen species (ROS) is considered as an effective antitumor treatment. Here, a liposomal formulation of dichloroacetic acid (DCA) and metal–organic framework (MOF)‐Fe2+ (MD@Lip) has been developed, which can efficiently stimulate ROS‐mediated cancer cell apoptosis in vitro and in vivo. MD@Lip can not only improve aqueous solubility of octahedral MOF‐Fe2+, but also generate an acidic microenvironment to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…In recent years, immunotherapy combined with nanotechnology, defined as nanoimmunotherapy, has shown promising performance for cancer therapy [ [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] ]. Among these therapeutics, metal-organic frameworks (MOFs), as a crystal material, has been widely studied in biomedical field [ [31] , [32] , [33] , [34] , [35] , [36] , [37] ]. MOFs of nanosized iron carboxylate, especially MIL101(Fe), have attracted considerable attention due to their excellent biocompatibility and biodegradability [ [38] , [39] , [40] ].…”
Section: Introductionsmentioning
confidence: 99%
“…In recent years, immunotherapy combined with nanotechnology, defined as nanoimmunotherapy, has shown promising performance for cancer therapy [ [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] ]. Among these therapeutics, metal-organic frameworks (MOFs), as a crystal material, has been widely studied in biomedical field [ [31] , [32] , [33] , [34] , [35] , [36] , [37] ]. MOFs of nanosized iron carboxylate, especially MIL101(Fe), have attracted considerable attention due to their excellent biocompatibility and biodegradability [ [38] , [39] , [40] ].…”
Section: Introductionsmentioning
confidence: 99%
“…The pH in the TME is 6.5–7, while the catalytic activity of MOF-Fe is extremely low in this physiological environment, which will limit the scope of its biological applications [ 37 ]. Some studies have shown that MOF-Fe catalysis of Fenton reaction can only be carried out in acidic media (pH is 2.0–5.0) [ 38 ]. To solve this problem, researchers designed pH-responsive MOFs that can regulate the TME.…”
Section: Classification and Featured Chemistry Of F-ncsmentioning
confidence: 99%
“…Lan et al, 2018). For instance, Sun et al reported a multifunctional nanoplatform by integrating dichloroacetic acid (DCA) into liposomal formulation and Fe-based MOF (MD@Lip), which can amplify the intratumoral ROS stress for management of the malignant tumors (L. Sun et al, 2019). The hybrid nanostructures could improve aqueous solubility of the octahedral MOFs, offering an acidic TME for Fenton reaction.…”
Section: Iron-based Nanomaterials For Cdtmentioning
confidence: 99%
“…Fe‐based metal‐organic frameworks (MOFs) possess high porosity and tuneable surface functionalities, which are promising for improving the performance of Fenton reaction (W. Cai et al, ; G. Lan et al, ). For instance, Sun et al reported a multifunctional nanoplatform by integrating dichloroacetic acid (DCA) into liposomal formulation and Fe‐based MOF (MD@Lip), which can amplify the intratumoral ROS stress for management of the malignant tumors (L. Sun et al, ). The hybrid nanostructures could improve aqueous solubility of the octahedral MOFs, offering an acidic TME for Fenton reaction.…”
Section: Nanomaterials For Cdtmentioning
confidence: 99%